Consecuencias epistemológicas de la adquisición del lenguaje infantil en las notas de Wittgenstein Sobre la certeza - Ariso, José María (Revista de Filosofía, 2010)
Wittgenstein’s remarks in On Certainty about the acquisition of child language have gone nearly unnoticed for the commentators of his work. In this paper, I analyze some of those remarks to shed light on the main questions posed in On the categorical distinction between knowledge and certainty; the nature of language-games; the refutation of skepticism and, above all, the challenges involved by learning to believe.
Keywords: Child language; Certainty; Knowledge; Doubt; Skepticism